Chronic Conditions, Fluid States: Chronicity and the Anthropology of Illness - Manderson, Lenore; Smith-Morris, Carolyn (Studies in Medical Anthropology, 2010)
Chronic Conditions, Fluid Statesexplores the uneven impact of chronic illness and disability on individuals, families, and communities in diverse local and global settings. To date, much of the social as well as biomedical research has treated the experience of illness and the challenges of disease control and management as segmented and episodic. Breaking new ground in medical anthropology by challenging the chronic/acute divide in illness and disease, the editors, along with a group of rising scholars and some of the most influential minds in the field, address the concept of chronicity, an idea used to explain individual and local life-worlds, question public health discourse, and consider the relationship between health and the globalizing forces that shape it.